If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x-(4x-5)=35
We move all terms to the left:
9x-(4x-5)-(35)=0
We get rid of parentheses
9x-4x+5-35=0
We add all the numbers together, and all the variables
5x-30=0
We move all terms containing x to the left, all other terms to the right
5x=30
x=30/5
x=6
| 5(x+4)+24x=9 | | -2x+14=-44 | | .9a+3.7=6.1-0.3a | | -2(x+6)+8=-4 | | -2.2x=11 | | 2x+8x-16=6x | | -19-16-19s=-7s+13 | | 4x=9x+3 | | 6.5x-13=45.5 | | -4.8=4.1y-3.6y-6.8 | | 7(p+3)+9=5(p–2) | | (4x+10)=5x+80 | | 2x+3(5x−7)=47 | | -6+6x+2=+12 | | -8x+-8+13x=5x+14 | | 20f=300 | | 2(5n-4)=20n-15-13 | | m-3=-3+3m+2m | | 20+5x=4x+10 | | 4x-8=15x-10-9x | | 9=1/4(6x+12 | | 9x+11=2x−10 | | 2x+4-12=24 | | x-7=13 | | -19-16-19s=—7s+13 | | 2n+6-2n=-12+3n | | n-1-8=-9+n | | 5x-2+7x=-10 | | 26-3d+7d=42 | | 2/12x-8=2 | | -5(4-2a)=-100 | | 50x-12x+17=21x+15-32 |